The Pessimistic Images in Sylvia Plath’s Selected Poems - Abdulameer Ketab, Athraa (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Sylvia Plath is generally distinguished as a confessional poet, since her literary writings represent an actual dramatization of her own experiences with her family members. She skillfully embodies her personal tragedy as basis for symbolic poetic imagination, promoting her own life into poetic language.